2020
DOI: 10.1186/s13017-020-00331-2
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal membrane oxygenation in trauma patients: a systematic review

Abstract: Background Extracorporeal membrane oxygenation (ECMO) has evolved considerably over the past two decades and has been gradually utilized in severe trauma. However, the indications for the use of ECMO in trauma remain uncertain and the clinical outcomes are different. We performed a systematic review to provide an overall estimate of the current performance of ECMO in the treatment of trauma patients. Materials and methods We searched PubMed and MEDLINE databases up to the end of December 2019 for studies on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 66 publications
0
59
0
2
Order By: Relevance
“…Extended advanced monitoring is suggested to detect early deterioration, ideally as a baseline before initiation of ECMO to prevent potentially deleterious bleeding or thromboembolic complications [ 201 , 202 ]. Using extracorporeal lung assist has been reported in various circuit compositions, with all of these reports describing feasibility without an increased risk of bleeding and survival benefits, as well as high survival rates [ 161 , 162 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 , 217 ]. Some authors even reported using it in severe bleeding situations [ 158 , 216 , 217 , 218 ].…”
Section: Factors Excluded As Contraindications/additional Contraindications Onlymentioning
confidence: 99%
See 1 more Smart Citation
“…Extended advanced monitoring is suggested to detect early deterioration, ideally as a baseline before initiation of ECMO to prevent potentially deleterious bleeding or thromboembolic complications [ 201 , 202 ]. Using extracorporeal lung assist has been reported in various circuit compositions, with all of these reports describing feasibility without an increased risk of bleeding and survival benefits, as well as high survival rates [ 161 , 162 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 , 217 ]. Some authors even reported using it in severe bleeding situations [ 158 , 216 , 217 , 218 ].…”
Section: Factors Excluded As Contraindications/additional Contraindications Onlymentioning
confidence: 99%
“…To gain the greatest benefit, a decision to initiate ECMO should not be delayed [ 209 , 213 , 214 , 219 ]. In particular, the injury severity score (ISS) did not show an influence on survival for patients treated with or without ECMO [ 203 , 204 , 206 , 207 , 210 , 211 , 212 ]. Therefore, ECMO should be initiated early in trauma patients if indicated, rather than considered a contraindication ( Table 9 ).…”
Section: Factors Excluded As Contraindications/additional Contraindications Onlymentioning
confidence: 99%
“…There were nine patients in whom heparin was not administered during ECMO application (three survivors [30.0%] and six non-survivors [40.0%]). In patients with multiple traumas, the chances of bleeding are high, mak- ing it challenging to use anti-hemostatic agents [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…There is much research needed on the proper initiation time for ECMO in the trauma patient and which patients will have the most benefit from ECMO. The safety and efficacy of ECMO still needs to be studied [20].…”
Section: Indications For Immediate Tracheal Intubationmentioning
confidence: 99%